Conditional Regard, Self-Concept, and Relational Authenticity: Revisiting Some Key Rogerian Concepts Cross-Culturally, Through Multilevel Modeling. (March 2020) - Lynch, Martin F.; Sheldon, Kennon M.
The present cross-cultural study utilized contemporary statistical techniques to explore the associations among conditional regard, ideal and actual self-concept, and relational authenticity, constructs with deep roots in the Rogerian and humanistic traditions. In three countries (China, Russia, and the United States), the experience of conditional regard in past and present relationships predicted larger discrepancies between ideal and actual self-concept, and lower feelings of authenticity within relationships. Implications for the study of self-concept and the development of self, as well as for practice, are discussed.